Organisational Communication and Employee Productivity in a Post Covid-19 Era: A Study of University of Uyo Teaching Hospital (UUTH) - Umoren, Philomena (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
This study was conducted to find out the manner of information flow within University of Uyo Teaching Hospital during and after the coronavirus outbreak, channels of communication are used for management – employee communication in University of Uyo Teaching Hospital during and after the coronavirus outbreak, relationship between communication flow and employees’ productivity in University of Uyo Teaching Hospital during and after the coronavirus outbreak; and, extent to which communication affect work performance in University of Uyo Teaching Hospital during and after the coronavirus outbreak. From the administrative unit of the Hospital, the total population of staff is 2,172, the sample size gotten was 389. The findings of the study included that most of the workers in UUTH strongly agreed that information in their department mostly comes from the heads (members of the management team), with very little presence of the flow of information vertical upward from employee to management in term of making decision. A majority of the employees strongly agreed that queries are the most sent form of communication in my department. Employees opined that their performance and productivity of workers in UUTH was not affected by negative communication among by colleagues as well as hostile communication from colleagues. Most of the workers in UUTH (66.6%) agree that communication affects work performance and productivity in University of Uyo Teaching Hospital to a very high extent. The researcher therefore recommended that top management staff should pay attention to positive communication, especially when there is a new task or need to correct and commend.